Textbook of Pathology for Allied Health Sciences - Nayak, R. Ramadas (Jaypee Brothers Medical Publishers, 2017)
This textbook focuses on pathology for allied health sciences. Pathology is a rapidly-expanding and ever-changing field and lays the foundation for understanding diseases. This book consists of 39 chapters and is organized into three sections namely General Pathology, Systemic Pathology and Clinical Pathology. Section 1 provides an overview of the basic pathologic mechanisms underlying diseases including cellular adaptations, inflammation, tissue repair, chronic inflammation, hemodynamic disorders, immunological disorders, neoplasia, genetics and radiation. Section 2 deals with systemic pathology with chapters devoted to diseases of various organ systems including vascular, cardiac, hematology, lymph nodes, respiratory, head and neck, gastrointestinal, liver and biliary tract, pancreas, urinary, male genital tract. Section 3 deals with clinical pathology with chapter on anticoagulants and hemoglobin estimation, blood cell counts, hematocrit, ESR estimation and peripheral blood smear examination, reticulocyte count, bone marrow examination, and sputum examination, semen analysis, urine analysis and stool examination. The text provides all the basic information; the student will ever need to know. Key points are shown in bold letters so that student can rapidly go through the book on the previous day or just before the examination.